Development, Validation, and Empirical Testing of an Innovative Metric For Assessing Lecturers' Pedagogical Efficacy Within Nigerian Higher Education Institutions - Ibrahim, Abdul-Wahab; Taura, Ali Abdullahi (Papanda Publisher, 2025)
This study developed and evaluated the reliability of the 30-item Lecturers' Teaching Effectiveness Scale (LTES) while investigating how university structure, gender, and teaching experience impact LTES scores. Employing an instrumental research design, the study targeted all in-service university lecturers in Nigeria. A sample of 2,400 lecturers was selected from six states representing the country’s geopolitical zones. The LTES, created following a thorough literature review, evaluates various facets of teaching effectiveness. Data were analyzed using Exploratory Factor Analysis, independent t-tests, One-Way ANOVA, and Scheffe Post hoc tests. After removing six items with low reliability, the refined 24-item LTES exhibited strong reliability, with a Cronbach's Alpha of 0.89 and a Split-half coefficient of 0.75, surpassing the original version. Consistent item-total statistics reinforced the scale's robustness. Results showed no significant impact of university structure or gender on LTES scores, indicating teaching effectiveness is unrelated to these factors. However, teaching experience significantly influenced scores, highlighting that experienced lecturers achieve higher effectiveness. Hence, the LTES introduces a refined, robust 24-item tool with high reliability, specifically designed to evaluate diverse facets of teaching effectiveness, while being unaffected by variables like university structure or gender. It was recommended that continuous efforts to support lecturers are essential for sustaining high levels of teaching effectiveness throughout their careers.